Inhibitory effect of calcium (derived from eggshell)-supplemented chocolate on absorption of fat in human males - Murata, T. (Osaka Medical Coll., Takatsuki (Japan)); Kuno, T; Hozumi, M; Tamai, H; Takagi, M; Kamiwaki, T; Itoh, Y (Nihon Eiyō, Shokuryō Gakkai shi, 1998)
We investigated the effects of calcium on absorption of fat from chocolate in human males. For three days nine human male adults (Ca-group) were administered 23 pieces of chocolate, each piece (8.0 g) containing 3.1 g of total fat and 150 mg of calcium (derived from eggshell), and a control group was administered the same chocolate without the calcium. All subjects were fed a diet containing a small quantity of fat. All feces were collected and analyzed for the levels of total lipid and fatty acids during the study period. The results were as follows: 1) The fecal levels of total lipid were significantly higher in the Ca-group than in the control group. 2) The fecal levels of palmitic and stearic acids were also higher in the ca-group. 3) There was a marked correlation between the concentration of fecal calcium and fecal total lipid. 4) No marked change was observed n serum lipid or calcium. These results suggest that the calcium in the chocolate combined particularly with saturated fatty acids in the digestive canal and inhibited their absorption although no change in serum lipids was observed in the short term